Antioxidant Capacity of Melatonin against Oxidative Stress Caused by Exercise-Induced Weight Loss in Rats - Recai Aci; Adem Keskin (Universitas Nahdlatul Ulama Surabaya, 2023)
Antioxidant supplements such as melatonin are used to prevent oxidative stress during exercise. This study aimed to investigate the antioxidant capacity of melatonin supplementation against oxidative stress induced by the weight loss observed during exercise. Forty Wistar Albino male rats were subjected to 10 days of jogging exercises. Two groups were formed based on weight loss. Two subgroups were created in each group. Melatonin (5 mg/kg) was administered to each subgroup in each group. The other subgroups were designated as control subgroups. Blood samples were collected after 10 d. Superoxide dismutase (SOD), total antioxidant status (TAS), glutathione peroxidase, melatonin, and malondialdehyde levels were analyzed in blood samples. SOD, glutathione peroxidase, TAS, and melatonin levels in the melatonin subgroup were higher than those in the control subgroup in the non-weight loss group. In contrast, the malondialdehyde levels were lower. Melatonin levels in the melatonin subgroup were higher than those in the control subgroup in the weight loss group. Conversely, the SOD and TAS levels were lower. In addition, there was a positive correlation between weight loss and malondialdehyde levels and a negative correlation with SOD, TAS, and melatonin levels. Melatonin (5 mg/kg) supplementation showed antioxidant capacity in exercise without weight loss, but was insufficient in exercise with weight loss.